2001
DOI: 10.1002/jcp.1088
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of reactive oxygen species in D‐galactosamine–induced sensitization against tumor necrosis factor‐α–induced hepatocyte apoptosis

Abstract: Intravenous administration of tumor necrosis factor-alpha (TNF-alpha) (0.5 microg/mouse) caused hepatocyte apoptosis in BALB/c mice when they were sensitized with D-galactosamine (GalN, 20 mg/mouse). Activation of nuclear factor kappa B (NF-kappa B) and expression of apoptotic Bcl-2 family members were not significantly different between livers of mice treated with TNF-alpha alone and GalN + TNF-alpha, indicating that neither activation of NF-kappa B nor expression of Bcl-2 family is involved in the sensitizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 45 publications
(60 reference statements)
5
27
0
Order By: Relevance
“…3A-B, upper panels), suggesting that TNF-␣ activated NF-B in hepatocytes in vivo as previously reported. 22 There was no nuclear translocation of p65 and no GFP expression in either the right or left lobe of PBDL livers (Fig. 3A-B, lower panels).…”
Section: Apoptotic Effect Of Tnf-␣ In Nf-b-suppressed Liver In Bdl MImentioning
confidence: 89%
“…3A-B, upper panels), suggesting that TNF-␣ activated NF-B in hepatocytes in vivo as previously reported. 22 There was no nuclear translocation of p65 and no GFP expression in either the right or left lobe of PBDL livers (Fig. 3A-B, lower panels).…”
Section: Apoptotic Effect Of Tnf-␣ In Nf-b-suppressed Liver In Bdl MImentioning
confidence: 89%
“…It has been reported that the PI 3-kinase/Akt pathway mediates hepatocyte survival (52). Selenoprotein P, which functions as a phospholipid hydroperoxide glutathione peroxidase, could protect TNF-␣-induced hepatocyte apoptosis (36).…”
Section: Discussionmentioning
confidence: 99%
“…In the HepG2 hepatoma cell line, which constitutively expresses IL-8 mRNA, AP-1 and PEA3 are shown to play important roles (15). In contrast, NF-B has been shown to be essential for expression of IL-8 in several types of cells, and TNF-␣ has been known as an activator of NF-B (29,30). In the present study, IL-8 production by TNF-␣ was inhibited by either Ad5IB or LY 294002.…”
Section: Discussionmentioning
confidence: 99%
“…However, hepatocytes are normally resistant to the cytotoxicity of TNF-␣. Administration of TNF-␣ alone does not induce hepatocyte apoptosis in mouse liver in vivo (25,29,31) or in cultured rat RALA (40) and human Hc (30) hepatocytes, suggesting that TNF-␣ also activates molecules that protect cells against apoptosis. For example, TNF-␣ transmits antiapoptotic signals via nuclear factor B (NF-B) and phosphatidylinositol 3-kinase (PI3K)/Akt.…”
mentioning
confidence: 99%